The WTO, Human Rights and hunger - Zabalo, Patxi (Revista Española de Desarrollo y Cooperación, 2023)
The persistence of hunger reveals the failure of the transnacional corporations-led agribusiness system, which takes advantage of World Trade Organization’s rules. It’s necessary to set up a new system to feed all human beings, along the lines of food sovereignty, agroecology and peasant economy.